How to face the scientific communication today. International challenge and digital technology impact on research outputs dissemination - Medici, Marco; Modugno, Valentina; Pracucci, Alessandro (Scuole di dottorato, 2017)
Dissemination of scientific results is an important and necessary component of research activity. Nowadays research asks to be widely diffused and shared in a larger community in the effort to demonstrate its innovation and originality, so to enlarge network and obtain funds to keep working. In this context, PhD students, as part of scientific community and young researchers in training, have to understand the rule of publications to define the best strategy for the dissemination of their research. The present book, through the experiences of national and international PhD candidates, PhDs and Professors, is a contribute in the current opened debate on the most effective strategies and related tools to design specific actions, to highlight and improve the peculiar qualities and disciplines of each research.